Single-sided water-based environment-friendly pyrograph film and preparation process thereof
By using the aqueous release layer made of modified aqueous acrylate and other components in the hot film, the problem of difficulty in peeling the ink absorbing layer and the release layer is solved, and the rapid detachment and stable adhesion of the ink absorbing layer during the thermal transfer process is achieved, which significantly improves the thermal transfer efficiency and product quality.
Patent Information
- Application Number
- CN202510106002.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-23
AI Technical Summary
When the existing hot film is transferred on a large area, it is difficult to peel off the ink absorbing layer and the release layer, resulting in uneven transfer and incompleteness, affecting the aesthetics and practicality of the product.
The aqueous release layer is made of modified aqueous acrylate, hydrogen-containing polysiloxane, phenyl hydroxyl mesh silicone, etc. The cured aqueous release layer enables the ink absorbing layer to quickly detach and adhere stably to the surface of the printing material during the thermal transfer process.
It significantly improves the thermal transfer efficiency and transfer effect, avoids the problem of residual ink absorbing layer, and improves the quality and aesthetics of the final product.
Abstract
Description
Technical Field
[0001] The present application relates to the field of thermal transfer films, and more specifically, to a single-sided water-based environmentally friendly heat transfer film and a preparation process thereof. Background Art
[0002] Common heat transfer films are made by the following steps: first, pre-printing a pattern or text on the heat transfer film, then sprinkling hot melt adhesive powder on one side of the pattern or text, shaking off the excess hot melt adhesive powder, and then baking at high temperature to make the hot melt adhesive powder completely melt and adhere to one side of the pattern or text, and forming an adhesive layer after solidification to make the heat transfer film; when in use, the pattern or text on the base film is transferred to a substrate, such as clothing, through the action of heat and pressure. Due to the presence of the adhesive layer, the pattern or text can be stably adhered to the substrate. Since the pattern or text of the heat transfer film is rich in layers, small in color difference, and good in reproducibility, it can achieve the effect required by the designer.
[0003] As a functional material widely used in clothing, decorations and other fields, heat transfer film has developed rapidly in recent years. The heat transfer film is mainly composed of an ink-absorbing layer, a release layer and a base layer, among which the release layer plays a key role, ensuring that the ink-absorbing layer and the pattern or text sprayed on the ink-absorbing layer can be smoothly transferred to the substrate during the thermal transfer process. However, with the continuous growth of market demand and technological advancement, the existing heat transfer film technology still has some shortcomings and needs to be improved to meet higher application requirements.
[0004] In the prior art, in order to achieve efficient transfer of heat transfer films, the methods commonly adopted include but are not limited to: (1) optimizing the selection of release layer materials, such as using different types of release agents to improve its peeling performance; (2) adjusting the thickness of the release layer to balance the transfer efficiency and stability; (3) changing the surface treatment method of the release layer, such as the coating method and curing conditions, to adjust its bonding force with the ink-absorbing layer; (4) improving the formulation of the ink-absorbing layer to enhance its tolerance and adhesion at high temperatures. Although these methods can solve the problem to a certain extent, they still face challenges in practical applications.
[0005] Although the above method improves the transfer effect of the heat transfer film to a certain extent, it still has obvious defects. Especially when transferring over a large area, due to the strong adhesion between the release layer and the ink absorbing layer, it is easy to make it difficult to peel off the ink absorbing layer and the release layer, or the ink absorbing layer partially remains on the surface of the release layer after peeling, which seriously affects the final transfer quality. In addition, the transferred pattern or text often has problems such as unevenness and incompleteness, which reduces the overall aesthetics and practicality of the product. Therefore, developing a new type of single-sided water-based environmentally friendly heat transfer film to solve these problems has become an important topic of current research. Summary of the invention
[0006] In order to improve the efficiency of thermal transfer and ensure the quality of the pattern after transfer, the present application provides a single-sided water-based environmentally friendly heat transfer film and a preparation process thereof.
[0007] In the first aspect, the present application provides a single-sided water-based environmentally friendly heat transfer film, which includes an ink-absorbing layer, a water-based release layer and a base layer from the upper surface to the lower surface, wherein the water-based release layer is obtained by curing a water-based release agent, and the water-based release agent is composed of the following raw materials in weight percentage: Modified waterborne acrylate 35-45 parts 40-50 parts of deionized water Crosslinking agent 10-15 parts Defoaming agent 1-1.5 parts 5-10 parts of modified polyurethane; The modified water-based acrylate is prepared from alkenyl siloxane, hydrogen-containing polysiloxane, phenyl hydroxyl network silicone resin, bonding aid, surfactant, initiator and water; The bonding aid is one or more of paraffin wax emulsion, palm wax emulsion and polytetrafluoroethylene emulsion.
[0008] By adopting the above technical solution, the modified water-based acrylate has good wetting and dispersibility and initial adhesion, and can stably adhere to the surface of the base layer and form a uniform water-based release layer thereon. The cured water-based release layer not only helps the ink-absorbing layer to detach quickly during the thermal transfer process, but also ensures the stable adhesion of the ink-absorbing layer on the surface of the substrate, effectively avoiding the uneven transfer and incomplete problems caused by the residual ink-absorbing layer. This significantly improves the thermal transfer efficiency and transfer effect, and improves the quality and aesthetics of the final product.
[0009] Specifically, alkenyl siloxane, hydrogen-containing polysiloxane, phenyl hydroxyl silicone resin and adhesive additive are compounded to achieve a synergistic effect and further improve the effect of the ink-absorbing layer quickly separating from the water-based release layer during thermal transfer, while ensuring that the water-based release layer formed after curing has stable adhesion to the base layer, thereby preventing the water-based release layer from separating from the base layer during thermal transfer, thereby affecting the overall thermal transfer quality.
[0010] In addition, by compounding the alkenyl siloxane, hydrogen-containing polysiloxane, phenyl hydroxyl network silicone resin, adhesive additive, etc. of the present application, the aqueous release agent obtained, after curing, is not only environmentally friendly, but also can ensure that within a relatively short period of time, its large-area ink-absorbing layer can be completely separated from the aqueous release layer and stably fixed on the substrate, avoiding the occurrence of defects and the like, thereby improving the quality of its pattern layer after thermal transfer, and at the same time ensuring the adhesion stability between the aqueous release layer and the base layer, reducing the phenomenon of defects in the aqueous release layer after thermal transfer.
[0011] Preferably, the bonding aid is composed of paraffin emulsion, palm wax emulsion and polytetrafluoroethylene emulsion in a weight ratio of 1:(1-3):(1-4).
[0012] By adopting the above technical scheme, the adhesive additive prepared by mixing paraffin emulsion, palm wax emulsion and polytetrafluoroethylene emulsion in a specific proportion can significantly improve the wettability and initial adhesion of the water-based release agent, so that the water-based release layer can be more evenly attached to the surface of the base layer, ensuring that the ink-absorbing layer is quickly and completely separated from the water-based release layer during the thermal transfer process, effectively avoiding the problem of ink-absorbing layer residue, and improving the transfer efficiency and transfer quality.
[0013] Preferably, the hydrogen-containing polysiloxane is hydrogen-terminated phenyl polysiloxane and / or fluorine-modified polysiloxane hydrogen-containing fluorosilicone oil.
[0014] By adopting the above technical scheme, hydrogen-terminated phenyl polysiloxane and / or fluorine-modified polysiloxane containing hydrogen fluorosilicone oil as the hydrogen-containing polysiloxane component can significantly improve the heat resistance and chemical stability of the water-based release agent, enhance the adhesion between it and the base layer, and ensure that the water-based release layer will not decompose or deteriorate during high-temperature baking, so that the ink-absorbing layer can be more stably separated from the water-based release layer during thermal transfer, reduce residue, and improve transfer quality and efficiency.
[0015] Preferably, the hydrogen-containing polysiloxane is composed of hydrogen-terminated phenyl polysiloxane and fluorine-modified polysiloxane hydrogen-containing fluorosilicone oil in a weight ratio of 1:(1-3).
[0016] By adopting the above technical solution, the hydrogen-containing polysiloxane is composed of hydrogen-terminated phenyl polysiloxane and fluorine-modified polysiloxane hydrogen-containing fluorosilicone oil in a weight ratio of 1: (1-3), so that the water-based release agent has better wetting and dispersibility and initial adhesion, so that it can adhere to the surface of the base layer more stably and form a uniform water-based release layer after curing. This not only improves the peeling performance between the ink-absorbing layer and the water-based release layer, but also ensures that the ink-absorbing layer can be quickly and completely transferred to the substrate during the thermal transfer process, avoiding the problem of residue, and significantly improving the thermal transfer efficiency and transfer effect.
[0017] Preferably, the phenyl hydroxy network silicone resin is a methylphenyl silicone resin containing silanol groups.
[0018] By adopting the above technical solution, methylphenyl silicone resin containing silanol groups is used as phenyl hydroxyl network silicone resin, which can significantly improve the wettability and dispersibility of the water-based release agent, so that the water-based release layer is more evenly attached to the base layer. This not only improves the stability of the water-based release layer, but also enhances the interfacial force between the ink-absorbing layer and the water-based release layer, ensuring that the ink-absorbing layer can be quickly and completely transferred to the substrate during the thermal transfer process, avoiding the problem of residue, thereby improving the thermal transfer efficiency and the final transfer effect.
[0019] Preferably, the alkenyl siloxane is (acryloxymethyl)dimethylmethoxysilane and / or methacryloxypropyltris(trimethylsiloxy)silane.
[0020] By adopting the above technical solution, (acryloxymethyl) dimethylmethoxysilane and / or methacryloxypropyl tris(trimethylsiloxy) silane as alkenyl siloxane can significantly improve the wetting and dispersibility and initial adhesion of the water-based release agent, making the water-based release layer more uniform and stable on the surface of the base layer. This not only improves the peeling performance of the ink-absorbing layer during thermal transfer, but also ensures that the ink-absorbing layer can firmly adhere to the surface of the substrate to avoid residue problems, thereby effectively improving the thermal transfer efficiency and transfer effect.
[0021] Preferably, the cross-linking agent is one or more of diacetone acrylamide, adipic acid dihydrazide, and hexamethylenediamine.
[0022] By adopting the above technical solution, the crosslinking agent is selected from one or more of diacetone acrylamide, adipic acid dihydrazide, and hexamethylenediamine, which can effectively promote the crosslinking reaction between the molecules of the water-based release agent and enhance the mechanical strength and heat resistance of the water-based release layer. This not only improves the stability of the water-based release layer, but also ensures that the ink-absorbing layer can quickly detach from the water-based release layer during the thermal transfer process and stably adhere to the surface of the substrate, thereby improving the thermal transfer efficiency and transfer effect.
[0023] Preferably, the modified polyurethane is a waterborne polyurethane resin.
[0024] By adopting the above technical solution, the modified polyurethane uses water-based polyurethane resin, which improves the stability of the water-based release agent, making it less likely to precipitate or delaminate during the coating process, ensuring the uniformity and consistency of the water-based release layer. This not only enhances the bonding force between the ink-absorbing layer and the water-based release layer, but also improves the clarity and adhesion of the pattern after thermal transfer, further improving the overall performance of the heat transfer film.
[0025] Preferably, the ink-absorbing layer is formed by coating ink-absorbing ink on the aqueous release layer and curing the ink-absorbing ink, and the ink-absorbing ink consists of an aqueous polyurethane resin, an adsorbent filler, a diluent, a stabilizer, and a curing agent.
[0026] By adopting the above technical solution, the ink-absorbing layer is formed by applying the ink-absorbing ink on the aqueous release layer and curing, and the ink-absorbing ink contains an aqueous polyurethane resin, an adsorbent filler, a diluent, a stabilizer and a curing agent. As the main film-forming material, the aqueous polyurethane resin has good adhesion and chemical resistance, ensuring a firm bond between the ink-absorbing layer and the aqueous release layer. The adsorbent filler enhances the ink-absorbing and color-retaining properties of the ink-absorbing layer, making the pattern or text clearer and brighter during the transfer process. The diluent helps to adjust the fluidity of the ink-absorbing ink, making it easier to evenly coat the aqueous release layer. The stabilizer improves the stability of the ink-absorbing ink to prevent deterioration during storage and use. The curing agent accelerates the curing process of the ink-absorbing ink, improves production efficiency, and also ensures the mechanical strength and durability of the ink-absorbing layer. These components work together to ensure that the ink-absorbing layer not only has excellent ink-absorbing properties, but also can quickly separate from the aqueous release layer during the thermal transfer process, and form a stable and lasting pattern or text on the surface of the substrate.
[0027] In a second aspect, a method for preparing a single-sided water-based environmentally friendly heat transfer film comprises the following steps: Water-based release agent: According to parts by weight, weigh the modified water-based acrylic resin and deionized water, mix them, and stir them evenly to obtain emulsion A; then add the crosslinking agent and defoaming agent to emulsion A, increase the speed, stir them evenly, and then add the modified polyurethane to obtain emulsion B, and then adjust the pH value of emulsion B to 6.2-8.2 to obtain a water-based release agent; The water-based release agent is coated on the substrate, baked and cured to form a water-based release layer on the substrate; then the ink-absorbing ink is coated on the water-based release layer, baked and cured to form an ink-absorbing layer on the water-washable release layer to obtain a heat transfer film.
[0028] By adopting the above technical solution, the preparation method of the water-based release agent is simple and efficient, ensuring that the components are fully mixed and evenly mixed, and improving the stability of the water-based release layer. Specifically: Preparation of water-based release agent: By mixing modified water-based acrylate, deionized water, cross-linking agent, defoaming agent and modified polyurethane in specific proportions and adjusting the pH value, the wetting, dispersibility and initial adhesion of the water-based release agent are effectively improved, so that it can stably adhere to the surface of the base layer to form a uniform water-based release layer.
[0029] Formation of water-based release layer: The prepared water-based release agent is coated on the substrate and baked to cure. The formed water-based release layer has good heat resistance and peeling properties, ensuring that the ink-absorbing layer can quickly separate from the water-based release layer during the thermal transfer process and firmly adhere to the surface of the substrate, avoiding residue problems and significantly improving the thermal transfer efficiency and transfer effect.
[0030] Formation of ink-absorbing layer: The ink-absorbing ink is coated on the solidified water-based release layer, and then baked and solidified again to form an ink-absorbing layer. This process ensures the quality and thickness consistency of the ink-absorbing layer, and further optimizes the overall performance of the heat transfer film.
[0031] In summary, the present application includes at least one of the following beneficial technical effects: 1. The water-based release layer is made of modified water-based acrylate, hydrogen-containing polysiloxane, phenyl hydroxyl network silicone resin and other ingredients. It has good wetting and dispersibility and initial adhesion, can stably adhere to the surface of the base layer, and form a uniform water-based release layer after curing, which effectively solves the problem that the ink-absorbing layer and the release layer are difficult to peel off when the heat transfer film is transferred over a large area; 2. The cured water-based release layer enables the ink-absorbing layer to quickly detach and stably adhere to the surface of the substrate during the thermal transfer process, avoiding the situation where the ink-absorbing layer remains on the surface of the release layer, and significantly improving the thermal transfer efficiency and transfer effect. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the embodiments.
[0033] Waterborne polyurethane resin, manufacturer Anhui Yuanchen New Material Technology Co., Ltd., model YC-305; Heat transfer printing ink: Brand model Aocai XP600; Castor oil modified polyol, brand: Shuer, model: 65522; The brand model of the curing agent is Covestro Imprafix 2794; The stabilizer is diethylene glycol; The defoaming agent is an organosilicon defoaming agent, and the brand model is Evonik TEGO AIREX 902W; Paraffin emulsion, brand Xiyu, model XY-30 The palm wax emulsion is a water-based carnauba wax emulsion, brand model Xinghong water-based wax B-20603; PTFE emulsion is PTFE dispersion emulsion, brand model: Juhua JF-4DCD; Hydrogen-terminated phenyl polysiloxane, brand: Maidehao, model: MDH 233; Fluorine-modified polysiloxane containing hydrogen fluorosilicone oil, Hangzhou Heyu Technology Co., Ltd. model FGY-402; Methylphenyl silicone resin containing silanol, brand model Longsheng Sihai SH-1068. Example
[0034] Example 1 A single-sided water-based environmentally friendly heat transfer film includes an ink-absorbing layer, a water-based release layer and a base layer from the upper surface to the lower surface, the ink-absorbing layer has a thickness of 10-200 microns, the base layer has a thickness of 50-500 microns, and the water-based release layer has a thickness of 10-50 microns. In this embodiment, the ink-absorbing layer preferably has a thickness of 30 microns; the base layer has a thickness of 200 microns, and the water-based release layer has a thickness of 20 microns. The base material is a PET base material.
[0035] The single-sided water-based environmentally friendly heat transfer film is prepared by the following method: The modified water-based acrylate is prepared by weight ratio of 8 parts of alkenyl siloxane, 5 parts of hydrogen-containing polysiloxane, 10 parts of phenyl hydroxy network silicone resin, 10 parts of bonding aid, 3 parts of initiator, 2 parts of surfactant and 62 parts of water; the bonding aid is paraffin emulsion; the hydrogen-containing polysiloxane is hydrogen-terminated phenyl polysiloxane; the phenyl hydroxy network silicone resin is methylphenyl silicone resin containing silanol groups; the initiator is ammonium persulfate; the surfactant is OP-10; the alkenyl siloxane is (acryloxymethyl) dimethylmethoxysilane.
[0036] Water-based release agent: According to the weight percentage of the water-based release agent, 35 parts of modified water-based acrylic resin were weighed and mixed with 50 parts of deionized water, and stirred at a speed of 300 r / min for 10 minutes to fully mix and obtain emulsion A; then 15 parts of cross-linking agent and 1.5 parts of defoaming agent were added to emulsion A, and the speed was increased to 3000 r / min, and stirred for 10 minutes to fully mix and obtain emulsion B, and then 10 parts of modified polyurethane were added to obtain emulsion B, and ammonia water was added and the pH value of emulsion B was adjusted to 8 to obtain a water-based release agent. The modified polyurethane is a water-based polyurethane resin. The cross-linking agent is diacetone acrylamide.
[0037] The ink-absorbing ink is composed of water-based polyurethane resin, adsorption filler, diluent, stabilizer and curing agent in a weight ratio of 50:20:15:5:1. The adsorption filler is aluminum oxide; the diluent is castor oil modified polyol, and the stabilizer is diethylene glycol.
[0038] A water-based release agent is coated on a substrate and baked at 110°C for 2 minutes to form a water-based release layer on the substrate; then an ink-absorbing ink is coated on the water-based release layer, the drying temperature is 85°C, the drying time is 1 hour, and an ink-absorbing layer is formed on the water-washable release layer to obtain a heat transfer film.
[0039] Example 2 The difference between Example 2 and Example 1 is that the amount of raw materials of the water-based release agent is different, as follows: In parts by weight, 40 parts of modified waterborne acrylic resin, 45 parts of deionized water, 13 parts of crosslinking agent, 1.2 parts of defoaming agent, and 6 parts of modified polyurethane.
[0040] Example 3 The difference between Example 3 and Example 1 is that the amount of raw materials of the water-based release agent is different, as follows: In parts by weight, 45 parts of modified waterborne acrylic resin, 40 parts of deionized water, 10 parts of crosslinking agent, 1 part of defoaming agent, and 5 parts of modified polyurethane.
[0041] Example 4 The difference between Example 4 and Example 2 is that the bonding aid is palm wax emulsion.
[0042] Example 5 The difference between Example 5 and Example 2 is that the bonding aid is polytetrafluoroethylene emulsion.
[0043] Example 6 The difference between Example 6 and Example 2 is that the bonding aid is composed of paraffin emulsion, palm wax emulsion and polytetrafluoroethylene emulsion in a weight ratio of 1:1:1.
[0044] Example 7 The difference between Example 7 and Example 2 is that the bonding aid is composed of paraffin emulsion, palm wax emulsion and polytetrafluoroethylene emulsion in a weight ratio of 1:2:3.
[0045] Example 8 The difference between Example 8 and Example 2 is that the bonding aid is composed of paraffin emulsion, palm wax emulsion and polytetrafluoroethylene emulsion in a weight ratio of 1:3:4.
[0046] Example 9 The difference between Example 9 and Example 2 is that the hydrogen-containing polysiloxane is a fluorine-modified polysiloxane containing hydrogen fluorosilicone oil.
[0047] Example 10 The difference between Example 10 and Example 2 is that the hydrogen-containing polysiloxane is composed of hydrogen-terminated phenyl polysiloxane and fluorine-modified polysiloxane hydrogen-containing fluorosilicone oil in a weight ratio of 1:1.
[0048] Embodiment 11 The difference between Example 11 and Example 7 is that the hydrogen-containing polysiloxane is composed of hydrogen-terminated phenyl polysiloxane and fluorine-modified polysiloxane hydrogen-containing fluorosilicone oil in a weight ratio of 1:1.
[0049] Example 12 The difference between Example 12 and Example 7 is that the hydrogen-containing polysiloxane is composed of hydrogen-terminated phenyl polysiloxane and fluorine-modified polysiloxane hydrogen-containing fluorosilicone oil in a weight ratio of 1:3.
[0050] Embodiment 13 The difference between Example 13 and Example 2 is that the alkenyl siloxane is methacryloxypropyl tris(trimethylsiloxy)silane.
[0051] Embodiment 14 The difference between Example 14 and Example 2 is that the alkenyl siloxane is composed of (acryloxymethyl)dimethylmethoxysilane and methacryloxypropyltris(trimethylsiloxy)silane in a weight ratio of 1:3.
[0052] Embodiment 15 The difference between Example 15 and Example 7 is that the alkenyl siloxane is composed of (acryloxymethyl)dimethylmethoxysilane and methacryloxypropyltris(trimethylsiloxy)silane in a weight ratio of 1:3.
[0053] Example 16 The difference between Example 16 and Example 11 is that the alkenyl siloxane is composed of (acryloxymethyl)dimethylmethoxysilane and methacryloxypropyltris(trimethylsiloxy)silane in a weight ratio of 1:3.
[0054] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that an equal amount of hydrogen-containing polysiloxane is replaced by phenyl hydroxy network silicone resin.
[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the phenyl hydroxy network silicone resin is replaced by alkenyl siloxane in equal amounts.
[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that an equal amount of alkenyl siloxane is replaced by phenyl hydroxyl network silicone resin.
[0057] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the bonding aid is replaced by alkenylsiloxane in equal amounts.
[0058] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that alkenyl siloxane and hydrogen-containing polysiloxane are replaced by phenyl hydroxy network silicone resin in equal amounts.
[0059] Performance testing Detection method / test method Test 1; The heat transfer films obtained in Examples 1-16 and Comparative Examples 1-5 were cut into experimental samples of 50*50 cm.
[0060] The heat transfer printing ink is sprayed onto the ink-absorbing layer of the heat transfer film (experimental sample) through a spraying device, and the spraying amount is 88g / m2 , a pattern layer is formed on the surface of the ink-absorbing layer, and then one side of the pattern layer is attached to the surface of the aluminum alloy plate. When the vacuum meter shows a vacuum of -0.1MPa, the temperature is 175°C, and thermal transfer is performed. The transfer time is 100s, so that the ink-absorbing layer peels off the water-based release layer and is thermally transferred to the surface of the aluminum alloy plate together with the pattern layer, and a pattern layer is formed on the aluminum alloy surface. Observe whether the pattern layer on the surface of the aluminum alloy plate is incomplete or bubbling, or whether residual glue appears on the water-based release layer. If the above situation does not occur, the transfer time is recorded as 100s; if the above problems occur, extend the transfer time by 20s each time until the pattern layer or water-based release layer on the surface of the alloy plate does not have the above phenomena, and record the corresponding time.
[0061] Test 2; The experimental samples obtained from Examples 1-16 and Comparative Examples 1-5 were subjected to the transfer method of Test 1, and the transfer time was 200s to obtain the pattern layer on the surface of the alloy plate, and the falling sand test method was used for detection. The test standard was based on GB / T5237-2008. The time when the pattern layer showed through was observed. The observation was made every 5 minutes. During the bottom-through test, any three positions of the pattern layer on the surface of each alloy plate were tested, one position was located at the center, one position was 5 cm close to any edge, and the other was optional. The average bottom-through time of the three positions was calculated, and then the difference was calculated. The difference was equal to the bottom-through time obtained from the test at the position minus the average bottom-through time. Finally, the absolute value was taken, and the average difference was calculated.
[0062] The above experimental data are shown in Table 1. Table 1 Experimental data of Examples 1-16 and Comparative Examples 1-5 Test items Transfer time (min) Average Difference Example 1 240 6.67 Example 2 240 6.67 Example 3 240 6.67 Example 4 240 6.67 Example 5 260 6.67 Example 6 220 3.67 Example 7 200 1.67 Example 8 220 3.67 Example 9 240 3.67 Example 10 160 0 Embodiment 11 140 0 Example 12 140 0 Embodiment 13 260 3.67 Embodiment 14 200 1.34 Embodiment 15 160 0 Example 16 100 0 Comparative Example 1 280 13.34 Comparative Example 2 280 13.34 Comparative Example 3 280 13.34 Comparative Example 4 280 20 Comparative Example 5 300 15 Combining Example 1 and Comparative Examples 1-5 and Table 1, it can be seen that the transfer time of Comparative Examples 1-5 is longer, and the average difference of Comparative Examples 1-5 is also greater than the average difference of Example 1, indicating that the modified water-based acrylate prepared by using alkenyl siloxane, hydrogen-containing polysiloxane, phenyl hydroxyl network silicone resin, adhesive auxiliary agent, surfactant and water in the present application, combined with the water-based release agent raw material system, can obtain better release performance, and can make the ink-absorbing layer fall off quickly and completely during thermal transfer, thereby improving the processing efficiency of thermal transfer and ensuring the quality after thermal transfer.
[0063] Combining Example 2 and Example 7-8 with Table 1, it can be seen that the thermal transfer time of Example 6-8 is shorter than that of Example 2, and the average difference of Example 6-8 is smaller than the average difference of Example 2, indicating that Example 6-8 adopts paraffin emulsion, palm wax emulsion, and polytetrafluoroethylene emulsion to compound, which plays a synergistic role and further improves the peeling effect of the heat transfer film during thermal transfer.
[0064] In combination with Example 2, Example 7, Example 11 and Table 1, the time and average difference of the bottom-transparent book of Example 11 are better than those of Example 2 and Example 7, indicating that the compounding of hydrogen-terminated phenyl polysiloxane and fluorine-modified polysiloxane containing hydrogen fluorosilicone oil, combined with paraffin emulsion, palm wax emulsion, polytetrafluoroethylene emulsion to prepare the bonding aid, and the raw material composition of the present application can obtain better results, while improving the transfer efficiency, ensuring the transfer quality.
[0065] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A single-sided water-based environmentally friendly heat transfer film, comprising an ink-absorbing layer, a water-based release layer and a base layer from the upper surface to the lower surface, characterized in that: The water-based release layer is obtained by curing the water-based release agent, and the water-based release agent is composed of the following raw materials in percentage by weight: Modified waterborne acrylate 35-45 parts 40-50 parts of deionized water Crosslinking agent 10-15 parts Defoaming agent 1-1.5 parts 5-10 parts of modified polyurethane; The modified water-based acrylate is prepared from alkenyl siloxane, hydrogen-containing polysiloxane, phenyl hydroxyl network silicone resin, bonding aid, initiator, surfactant and water; The bonding aid is one or more of paraffin wax emulsion, palm wax emulsion and polytetrafluoroethylene emulsion.
2. The single-sided water-based environmentally friendly heat transfer film according to claim 1, characterized in that: The bonding aid is composed of paraffin emulsion, palm wax emulsion and polytetrafluoroethylene emulsion in a weight ratio of 1:(1-3):(1-4).
3. The single-sided water-based environmentally friendly heat transfer film according to claim 1, characterized in that: The hydrogen-containing polysiloxane is hydrogen-terminated phenyl polysiloxane and / or fluorine-modified polysiloxane hydrogen-containing fluorosilicone oil.
4. The single-sided water-based environmentally friendly heat transfer film according to claim 3, characterized in that: The hydrogen-containing polysiloxane is composed of hydrogen-terminated phenyl polysiloxane and fluorine-modified polysiloxane hydrogen-containing fluorosilicone oil in a weight ratio of 1:(1-3).
5. The single-sided water-based environmentally friendly heat transfer film according to claim 1, characterized in that: The phenyl hydroxy network silicone resin is a methylphenyl silicone resin containing silanol groups.
6. The single-sided water-based environmentally friendly heat transfer film according to claim 1, characterized in that: The alkenyl siloxane is (acryloxymethyl)dimethylmethoxysilane and / or methacryloxypropyltris(trimethylsiloxy)silane.
7. The single-sided water-based environmentally friendly heat transfer film according to claim 1, characterized in that: The cross-linking agent is one or more of diacetone acrylamide, adipic acid dihydrazide and hexamethylenediamine.
8. The single-sided water-based environmentally friendly heat transfer film according to claim 1, characterized in that: The modified polyurethane is a waterborne polyurethane resin.
9. The single-sided water-based environmentally friendly heat transfer film according to claim 1, characterized in that: The ink-absorbing layer is formed by coating ink-absorbing ink on the aqueous release layer and curing the ink-absorbing ink, and the ink-absorbing ink is composed of aqueous polyurethane resin, adsorbent filler, diluent, stabilizer and curing agent.
10. A single-sided water-based environmentally friendly heat transfer film according to any one of claims 1 to 9, characterized in that: The following steps are involved: Water-based release agent: According to parts by weight, weigh the modified water-based acrylic resin and deionized water, mix them, and stir them evenly to obtain emulsion A; then add the crosslinking agent and defoaming agent to emulsion A, increase the speed, stir them evenly, and then add the modified polyurethane to obtain emulsion B, and then adjust the pH value of emulsion B to 6.2-8.2 to obtain a water-based release agent; The water-based release agent is coated on the substrate, baked and cured to form a water-based release layer on the substrate; Then, the ink-absorbing ink is coated on the water-based release layer, baked and cured, and an ink-absorbing layer is formed on the water-washable release layer to obtain a heat transfer film.
Citation Information
Patent Citations
Heat transfer printing water-based release agent and preparation method thereof
CN114437609A
PET printing film material and preparation method thereof
CN116039279A
Package printing process based on release film and water-based resin plastic oil
CN118952871A
Thermal transfer printing type composite film and preparing method thereof
KR100844385B1
Hydroxyl polyacrylate emulsion and preparation method and application thereof
WO2017020513A1
Cited By
DTF white ink pyrograph film with surface lines
CN120840275A
Dtf white ink transfer film with surface texture
CN120840275B
Heat-tearable PET release film for pyrograph transfer printing and preparation method of heat-tearable PET release film
CN121912737A